The relationship between parental work and child growth and development - Sunarsih, Tri; Astuti, Endah Puji; Sahnti, Elvika Fit Ari; Abidah, Alief Nur Insyiroh (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: The parent's occupation factor is important because it can influence the quality of parenting, economic conditions, and family environment, all of which contribute to child development.Objective: This study aims to identify and analyze the relationship between parental economic status, namely parental employment, and child growth and development.Method: The research uses survey methods with a quantitative approach. Data was collected from respondents of mothers with children aged 0-5 years. Data analysis was carried out using the Chi-Square test to determine the significance of the relationship between parental employment and children's growth and development.Results: The study's results show a significant relationship between fathers' work and child growth, where children of fathers who work as laborers have the most normal growth. Meanwhile, maternal employment has a significant relationship with child development, with the highest normal development in children of mothers who do not work. However, maternal employment did not show an important relationship with child growth.Conclusion: This study concludes that the father's work has more influence on children's physical growth, while the mother's work has more influence on child development. These results show that parental employment characteristics have important implications for child development